THE “HOMOGENIZATION PROCESS” IN ROMANIA - STOENESCU, Roxana (Studia Universitatis Babes-Bolyai Studia Europaea, 2020)
The present research examines the relationship between the development of the nation state and homogenization efforts in Romania. On the one hand, this requires examining the establishment of ideological and dictatorial power practices that emerge from the historical context of capitalist and imperialist developments. On the basis of which the national conceptions of a closed body evolved, and thus certain groups, experienced because of their otherness compared to the national similarities, social exclusivity. Thus, the racial ideological attitudes and the resulting homogenization and repression policies of the dictatorships of the 20th century emerged. The aim of this work is to show how the homogenization process took place in Romania.